Exploring pre-service teacher' views of science process skills. Issue 1 (1st January 2022) - Nursalam, L O; Syarifuddin,; Sailan, Z; Saifullah,; Hakim, A R; Rosadi, A; Suhardi, M; Asyş_ari, M; Prayogi, S; Bilad, M R
Abstract: The school curriculum in Indonesia requires students to master science comprehensively through problem-based learning with the integration of science process skills (SPS) or scientific methods. This study aims to identify the responses of pre-service teacher students about the importance of SPS components. The data collection was done via a survey with samples of 120 pre-service teachers. The response of pre-service teacher to SPS was collected using 14 items in the questionnaire. The responses were analyzed qualitatively and statistically to find out the frequency of the strongest responses towards the SPS components. The results showed that pre-service teachers stated that problem-solving/critical thinking skills (63 voters), basic understanding answers (59 voters), hypotheses (41 voters), and making conclusions (39 voters) were key components in SPS. Based on these findings, the application of learning that can improve the science process skills of pre-service teachers is important to do.